Supratrochlear Neuralgia: A Prospective Case Series of 15 Patients. Issue 9 (18th August 2017) - Pareja, Juan A.; López‐Ruiz, Pedro; Mayo, Diego; Villar‐Quiles, Rocío‐Nur; Cárcamo, Alba; Gutiérrez‐Viedma, Álvaro; Lastarria, Carlo P.; Romeral, María; Yangüela, Julio; Cuadrado, María‐Luz
Abstract : Objective: The aim of this study was to describe clinical features unique to supratrochlear neuralgia. Background: The supratrochlear nerve supplies the medial aspect of the forehead. Due to the intricate relationship between supraorbital and supratrochlear nerves, neuralgic pain in this region has been traditionally attributed to supraorbital neuralgia. No cases of supratrochlear neuralgia have been reported so far. Methods: From 2009 through 2016, we prospectively recruited patients with pain confined to the territory of the supratrochlear nerve. Results: Fifteen patients (13 women, 2 men; mean age 51.4 years, standard deviation 14.9) presented with pain in the lower paramedian forehead, extending to the eyebrow in two patients and to the internal angle of the orbit in another. Pain was unilateral in 11 patients (six on the right, five on the left), and bilateral in four. Six patients had continuous pain and nine described intermittent pain. Palpation of the supratrochlear nerve at the medial third of the supraorbital rim resulted in hypersensitivity in all cases. All but one patient exhibited sensory disturbances within the painful area. Fourteen patients underwent anesthetic blockades of the supratrochlear nerve, with immediate relief in all cases and long‐term remission in three. Six of them had received unsuccessful anesthetic blocks of the supraorbital nerve. Five patients were treated successfully with oral drugs and one patient was treated with radiofrequency. Conclusions: Supratrochlear neuralgia is an uncommon disorder causing pain in the medial region of the forehead. It may be differentiated from supraorbital neuralgia and other similar headaches and neuralgias based on the topography of the pain and the response to anesthetic blockade.